(untitled) (Journal of Engineering Science, 2024)
ZnO nanoparticles (NPs) having nsemiconducting properties are important nanocatalysts for many surface reactions. Because of their extensive use as heterogeneous nanocatalyst for energy production and environmental cleaning, it is essential to understand their surface properties to design better chemical and photochemical nanocatalysts. Here, we used the sol-gel method to develop numerous ZnO NPs at various calcination temperatures (300 - 800 oC) and analyzed by different surface characterization techniques such as FTIR, SEM, XRD and UV-visible absorption spectroscopy. To investigate the catalytic activity a series of photooxidation studies on Remazol Red RR (RRR) were carried out at different conditions. From the surface characteristic analysis, it is found that the crystalline ZnO NPs are formed at above 400 oC temperature. The highest photocatalytic efficiency is found at 500 oC which might be related to the lowest particle size (35.4 ± 5.2 nm) and surface heterogeneity. The experimental results suggest that temperature-controlled growth rate and intra/inter-particle heterogeneity of ZnO nanoparticles have a great impact on the surface properties and photocatalytic activity. In addition to surface area, surface defects and crystal deformation may have a considerable impact on the photocatalytic activity by ZnO NPs. Finally, this study will help to understand what type of surface properties need to optimize to design industrial suit ZnO nanocatalysts. Journal of Engineering Science 15(1), 2024, 75-81